(untitled) (Journal of Rashid Latif Medical College, 2022)
Objective: The blood group system (ABO) and Rhesus genes (Rh) phenotypes vary widely between populations and ethno-geographical areas.The present study aimed to determine the distribution of ABO and Rh groups in a subset of population from Lahore, Pakistan. Methodology: The study included 1000 subjects (76.1% males and 23.9% females) from INMOL hospital, Lahore. Forward grouping was performed by using antigen-antibody agglutination method. Results: The distribution of phenotypes in the total sample was 23.9%, 35.2%, 8.8% and 32.1% for groups A, B, AB and O respectively. However, the seroprevalence of Rh positive (R) and Rh negative (r) was 91.7% and 8.3%, respectively. Conclusion: It was concluded that blood group B had highest prevalence and AB was the least frequent in population from Lahore and surroundings. This data may be helpful in keeping record for the management of availability of blood for crises. Also, it represents the variety in allele distribution in this population.